Konsentrasi Spermatozoa Mencit (Mus Musculus) Swiss Webster L. setelah Pemberian Serbuk Rimpang Kunyit (Curcuma Domestica) dengan Dosis Kronik - Djaelani, Muhammad Anwar (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The aim of this research was to prove the side effect of C.domestica rhizomes on M. musculus spermatogenesis. The effect was determined by sperm concentration differences between control and treatment group. Male M. musculus were divided into three groups, there are control group, positive control group and treatment group. Treatment were given orally with chronic exposure during 60 days. The samples were isolated from pars caudalis epidydimis at 13th, 61st and 73rd day of treatment. The result showed that there was a siginificantly diference between control group and treatment, but there were no differences between control group and positive control group. It could be concluded that the C.domestica rhizomes potentially influence M.musculus spermatogenesis.